Pemajuan Kebudayaan sebagai Desa Mandiri Melalui Peningkatan Ketahanan Budaya di Desa Nagarawangi Sumedang - Nyai Kartika; Reiza D. Dienaputra; Susi Machdalena; Prima Agustina Mariamurti; Witakania Sundasari Som; Rony Hidayat Sutisna (Universitas Hamzanwadi, 2025)
This study concerns the Promotion of Culture as an Independent Village through the Improvement of Cultural Resilience. The problem in villages that possess culture is the lack of inventory and documentation related to renewable cultural promotion objects (OPK), because conditions in the field may mean that these cultural promotion objects are still developing, underdeveloped, or even no longer developing. Through this research, it is hoped that the potential of OPK in Nagarawangi Village, Rancakalong District, Sumedang Regency, can be mapped comprehensively. The method used is qualitative research, with sources collected not only in the form of objects and written sources but also oral and visual sources. Oral sources were explored through interviews with storytellers as OPK actors and activists. As for visual sources, the exploration was not only carried out on visual sources in the form of moving images but also visual sources in the form of still visuals. The results of this study show a new approach to village development. The Cultural Advancement Village not only enriches the various existing approaches to village development but also provides a new space for village development, namely cultural space. The novelty of this approach will not only make villages more concerned about their culture but also enable villages to become centers of advancement.